The role of microstructure and grain orientations on intergranular cracking susceptibility of UNS 17400 martensitic stainless steel. (September 2017) - Masoumi, Mohammad; Tavares, Sérgio Souto Maior; Pardal, Juan Manuel; Martins, Tabatta Regihna Brito; Gomes da Silva, Marcelo José; de Abreu, Hamilton Ferreira Gomes
Abstract: The aim of this work was to investigate the role of crystallographic orientations and grain boundary characteristics as a new approach to controlling the intergranular cracking (IGC) susceptibility. In this respect, hydrogen cathodic charging under two different current densities was carried out on 17–4 pH steel (H900 condition) in order to search for correlations between intergranular corrosion and microstructure, inclusions, and grain orientations. Then, to emphasize the importance of crystallographic orientation in IGC, hydrogen cathodic charging was carried out on 17–4 pH steel in solution condition, in which grains oriented with 110 and 111 parallel to the normal direction (ND) are dominant. The results showed that a reduction in the fraction of undesired 001//ND grains and development of 110, 112, and 111//ND texture components improved the IGC resistance. In addition, a higher fraction of low angle and special boundaries with low internal energy due to better compatibility between adjacent grains was observed in the uncracked sample and led to increased IGC resistance. Highlights: A new approach to control intergranular cracking susceptibility is investigated. The role of crystallographic orientations and grain boundary characteristics. Grains correctly oriented with texture fibres improve IGC resistance. Grain boundary types play a major role in IGC susceptibility. LAGBs and CSL boundaries with low internal energy led to increase IGC resistance.